Kashir Zabaan adab ti culture Kashmiri Language, Literature and Culture - (:unkn) unknown (My University, 2019)
This Volume is a collection of twenty one papers by eminent scholars, on various aspects of Kashmiri language, literature and culture. Most of these papers were presented in two national seminars organised by Northern Regional Language Centre, Patiala in 2000 and 2001 at Patiala and New Delhi. The subjects of seminars held in Patiala and Delhi were to study the developement of Kashmiri language and literature after 1947 and Current trends and status of Kashmiri language and literature after 1947 and Current trends and status of Kashmiri Language, literature and culture respectively. Some of these papers have been specially written for the volume by scholars.
Kashmiri Language, Literature and Culture
Keywords: Kashmiri; English